Effects of tunable, 3D-bioprinted hydrogels on human brown adipocyte behavior and metabolic function. (15th April 2018) - Kuss, Mitchell; Kim, Jiyoung; Qi, Dianjun; Wu, Shaohua; Lei, Yuguo; Chung, Soonkyu; Duan, Bin
Graphical abstract: Abstract: Obesity and its related health complications cause billions of dollars in healthcare costs annually in the United States, and there are yet to be safe and long-lasting anti-obesity approaches. Using brown adipose tissue (BAT) is a promising approach, as it uses fats for energy expenditure. However, the effect of the microenvironment on human thermogenic brown adipogenesis and how to generate clinically relevant sized and functioning BAT are still unknown. In our current study, we evaluated the effects of endothelial growth medium exposure on brown adipogenesis of human brown adipose progenitors (BAP). We found that pre-exposing BAP to angiogenic factors promoted brown adipogenic differentiation and metabolic activity. We further 3D bioprinted brown and white adipose progenitors within hydrogel-based bioink with controllable physicochemical properties and evaluated the cell responses in 3D bioprinted environments. We used soft, stiff, and stiff-porous constructs to encapsulate the cells. All three types had high cell viability and allowed for varying levels of function for both white and brown adipocytes. We found that the soft hydrogel constructs promoted white adipogenesis, while the stiff-porous hydrogel constructs improved both white and brown adipogenesis and were the optimal condition for promoting brown adipogenesis. Consistently, stiff-porous hydrogel constructs showed higher metabolic activities than stiff hydrogel constructs, as assessed by 2-deoxy glucose uptake (2-DOG) and oxygen consumption rate (OCR). These findings show that the physicochemical environments affect the brown adipogenesis and metabolic function, and further tuning will be able to optimize their functions. Our results also demonstrate that 3D bioprinting of brown adipose tissues with clinically relevant size and metabolic activity has the potential to be a viable option in the treatment of obesity and type 2 diabetes. Statement of Significance: One promising strategy for the treatment or prevention of obesity-mediated health complications is augmenting brown adipose tissues (BAT), which is a specialized fat that actively dissipate energy in the form of heat and maintain energy balance. In this study, we determined how pre-exposing human brown adipose progenitors (BAP) to angiogenic factors in 2D and how bioprinted microenvironments in 3D affected brown adipogenic differentiation and metabolic activity. We demonstrated that white and brown adipogenesis, and thermogenesis were regulated by tuning the bioprintable matrix stiffness and construct structure. This study not only unveils the interaction between BAP and 3D physiological microenvironments, but also presents a novel tissue engineered strategy to manage obesity and other related metabolic disorders.